Diamond monohydride: the most stable three-dimensional hydrocarbon1. Issue 27 (21st July 2015) - Kondrin, Mikhail V.; Brazhkin, Vadim V.
<x xml:space="preserve">Abstract</x> We have proposed the crystal structure of a three-dimensional completely covalently bonded hydrocarbon with cohesive energy comparable to those of benzene and graphane.